(untitled) (LEARNing Landscapes, 2011)
Funding agencies are restructuring programs, rewriting priorities, and restating accountability demands all founded on the very basic point that research funded by public tax dollars must be relevant and accountable to diverse publics.This new wave of accountability challenges researchers to "translate" and "mobilize" knowledge so that research is understood by those publics and makes a difference in people’s lives. While goals of research accessibility are laudable, we argue that researchers’ goals need not be focused on finding better ways to translate knowledge for public consumption. Rather, the time has come for inquiry to be more about actively engaging people in meaning making. As a community of researchers with long-standing commitment to using the arts in research as a vehicle for engagement, this is an opportunity for us to provide leadership in this area.